Nurturing young minds: English is fun - Ibrahim, Syazliyati; Amat, Rafidah; Nur Morat, Berlian; Harun, Robekhah; Md Tahir, Norlizawati; Hasan, Asrol; Abu Hassan, Nor Asni Syahriza; Mansor, Nur Syazwanie; Badri, Zawani; Abd Rahim, Mas Aida (Universiti Teknologi MARA, Kedah, 2024)
Corporate social responsibility is currently in currency at various higher education institutions. This is relevant to the government’s aspiration in attempting to close the gap between universities and communities. One of the efforts taken to get closer to the community is by reaching out to establishments offering preschool education to young learners. The project is named English is Fun and designed to cater to young learners. This project is voluntarily conducted by a group of English language lecturers and a designer at kindergartens in the neighbouring area. The project involved preschool students, organised as a half-day activity, requiring the students to sing along, dance and complete an originally created puzzle on human body parts. This far, two series of English is Fun has been conducted. Questionnaire surveys were given to the participants and all students who joined the activities gave positive feedback. The kindergarten teachers who also joined as helpers during the session were also encouraging and agreed that such initiatives had benefited their students. In the future, the efforts can be expanded with other activities at the same neighbouring preschool establishment or similar activities can be conducted at other kindergartens in other areas. Either way, the bottom line is universities should give back to the communities by offering voluntary services that are practical, easy to execute and economical.